Circulate - Kou, Ying (Nanyang Technological University, 2020)
Circulate is an experimental illustration project based on the poetry Jian Zi Mu Lan Hua · Shuang Long Dui Qi, written by Su Shi. It used the poetic imagery and music to portray his emotional changes after some unexpected events.